Bronchopulmonary complications of measles in children (family case) - O. V. Molochkova; O. B. Kovalev; O. V. Shamsheva; N. O. Ilyina; M. A. Kosyreva; O. Yu. Brunova; A. A. Mayatskiy; A. A. Korsunskiy; O. A. Kashchenko; E. V. Galeeva (Детские инфекции (Москва))
Two clinical observations of measles in sisters old 1 year 10 months and 3 years and 8 months have been described. Measles was severe with the development of an early complication in the form of severe bilateral community-acquired pneumonia with pulmonary edema and severe respiratory failure 2 degrees, which required treatment in the intensive care unit. At the sisters measles proceeded on the background of persistent herpetic (cytomegalovirus and HHV-6) infections, and at older sister measles was on the background of pyoderma. Measles was confirmed by detection of specific IgM by ELISA. The sisters were not vaccinated against measles and had home contact with a younger sister who had an infection with a clinical of measles.